Age, period and cohort processes in chronic obstructive pulmonary disease related emergency department visit rate in Taiwan, 2001–2015 - I.-Shiang Tzeng; Wan-Chung Hu; Chih-Wei Wu; Meng-Yu Wu; Giou-Teng Yiang; Po-Chun Hsieh; Wen-Lin Su (Journal of Infection and Public Health)
Purpose: Emergency room (ER) physicians must deal with patients with clinically suspected symptoms, such as dyspnea, cough, and increased sputum production, on the frontlines of medical care if patients present with severe chronic obstructive pulmonary disease (COPD). This study aims to investigate the longitudinal tendencies of COPD-related ER visits. Patients and methods: A total of 360,313 patients were included in this study. The COPD-related ER visit rates between 2001 and 2015 were categorized using the International Classification of Disease (ICD) codes (496). The effects of age, period, and cohort on COPD-related ER visit rates were determined using an age-period-cohort (APC) model. Results: Age was associated with a high risk of COPD in the pediatric and older populations. A significant increase was observed in the period effect, from 2001 to 2015. The cohort effect tended to oscillate from 1918 to 1973, and was reversed in the latest cohort. Furthermore, the COPD-related ER visit rate increased between 2001 and 2015 in both men and women. Conclusion: Age, period, and cohort were observed to increase COPD visit rates. The APC model can be used to determine trends in COPD-related ER visits.